CONSTITUENTSOFPRUNUS ARMENIACA - Ahmed, Rehana; Rashid, Fahima; Mansoor, Sarwat; Ansar, Nasir (Biological Sciences - PJSIR, 2004)
Phytochemical screening of the non-alcoholic extract of Prunusarmeniaca has revealed the presence of a triterpenoid belonging to Ursane / Oleanane series and a steroid alongwith its glucoside for the first time from this source. Structures were confirmed by spectroscopic methods, using IR, 1H-NMR,13C-NMR and Mass spectra.